Relasi Pengetahuan Islam Eksoteris dan Esoteris - Syafaq, Hammis (Program Studi Filsafat Agama Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2012)
This article scrutinizes the relationship of Islamic knowledge focusing on esoteric realm and exoteric area or what so-called duality of life. Within intellectual treasures of Islam this dualism have subsequ-ently beat each other. It is sometimes in the form of friction between the scientific and non-scientific, rational and spiritual, the sacred and the profane, theocentric and anthropocentric. However, when carefully understood, the dualism shares the same nature, namely outer and inner aspects. The outer is represented by naming, while the inner can only be understood through the process of interpretation. In other words, these two aspects are represented by two words are name (outer aspect) and meaning (inner aspect). Therefore, Islam is present and it attempts to draw both together. As can be observed in this century, the mentality of modern humans seem to be eroded far from religious norms as people have developed science which leads to religious emptying from its noble values. Therefore, it is important to bring the esoteric realm into modern thought which tends only to put emphasis on exoteric aspect.